Embedded Fuzzy Based Boiler Control - Celin S (IAES International Journal of Robotics and Automation (IJRA), 2016)
Boiler control in a power station is a very important criteria in regulation of uninterrupted electricity. In existing power plants, the control of its features and parameters are done by PI and PD controllers. The parameters that control the regulation of boiler conduction are drum level, steam flow, feed water flow, steam temperature and light intensity. It is necessary to produce the steam required to run the generator. When the load in the generator changes, there must be corresponding change in the steam volume. This may cause adverse effect in the boiler. In order to avoid the effect in the boiler, the parameters mentioned above must be maintained constant, which is attained by regulating the corresponding valves. This project work has a feasibility of using fuzzy logic controllers in the place of conventional controllers is done by using embedded system. It is found that the rule based fuzzy logic technique can be implemented by stringent operating conditions.